Sustainable Tourism Development Model Based on Newa for Tourism Villages in Badung Regency - Darsana, I Made; Putu Eka Wirawan; I Made Bram Sarjana; I Dewa Made Adi Artha (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2025)
The tourism industry in Badung Regency has grown and developed very rapidly. However, this rapid progress is also accompanied by problems in the form of disparities in tourism development between regions and the emergence of overtourism phenomena. South Badung has advanced significantly in tourism infrastructure and facilities, whereas North Badung, which is rich in natural and cultural potential, still lags behind in tourism management. To prevent the widening gap in tourism development, a tourism development model oriented towards sustainable tourism is required, with a focus on the tourism villages in North Badung. One model projected to become a trend in future sustainable tourism is the Nature, Ecotourism, Wellness, and Adventure (NEWA) Tourism concept. This study aims to develop a sustainable tourism development model based on NEWA for tourism villages in Badung Regency. The study was conducted in 17 tourism villages in Badung Regency using a qualitative approach through document studies, observation, interviews, and focused group discussions. The data analysis methods used include descriptive analysis, SWOT, AHP, and QSPM. The results indicate that tourism villages in North Badung have diverse potential to be further developed based on NEWA Tourism. This study produces several sustainable tourism development models for tourism villages, namely: 1) a tourism village development model focusing on three main pillars: institutional strengthening, infrastructure improvement, and community participation; 2) a NEWA tourism product development model emphasizing inter-village collaboration and tourism product differentiation; and 3) a promotion development model highlighting the use of digital technology to expand market reach.. Keywords: Badung, tourism village, NEWA, sustainable tourism.